2016
DOI: 10.1080/21655979.2016.1235102
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin silicointeraction of porcine α-amylase withVicia fabacrude seed extract and evaluation of antidiabetic activity

Abstract: Diabetes mellitus is a group of metabolic disorder of glucose metabolism. The proper management of blood glucose level is an indicator in the treatment of this complex pathology. The aim of the present study was to evaluate the inhibitory potential of Vicia faba crude seed extracts on the activities of a-amylase. Phytochemical screening, FTIR and HPLC analysis confirmed the presence of a phenolic compound with percentage yield of 9.87% in the acetone extract. Acetone extract of seed had highest inhibitory pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…However, the result we got in the present study is similar to several other documentation on the antioxidant therapy in the management of diabetes [67]. Recently, Gudise et al (2019) also demonstrated that Argyreia pierreana and Matelea denticulata leaf extracts possess high antioxidant and antidiabetic potential which contains a high content of polyphenols [69].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the result we got in the present study is similar to several other documentation on the antioxidant therapy in the management of diabetes [67]. Recently, Gudise et al (2019) also demonstrated that Argyreia pierreana and Matelea denticulata leaf extracts possess high antioxidant and antidiabetic potential which contains a high content of polyphenols [69].…”
Section: Discussionsupporting
confidence: 90%
“…Identification and elucidation of polyphenols in the F-D was confirmed due to strong O-H and H-bonded stretching which is representing the phenols and alcohol functional groups. Similar results are reported by Choudhary and Mishra [67]. The peak at 2924.09 cm −1 and 2854.65 cm −1 is a strong C-H bonding stretch due to ether linkage and it indicates the adsorbed on the surface of F-D fraction.…”
Section: Discussionsupporting
confidence: 88%
“…Among five compounds like 2caffeoyl-L-tartaric acid, N-(E)-Caffeoyl dopamine, rosmarincacid, methyl rosmarinate,6,7,8,3',4pentamethoxy flavone and molecular docking indicated that the affinity energy of identified compounds among them rosmarinc caid which shows antidiabetic activity (50). Dhiraj Kumar Choudhary et al, have reported In-Silico molecular docking interaction of methanol, acetone extract which gives porcine from Vicia faba crude seed extract and evaluate antidiabetic activity with α-amylase by hydrogen bonding and hydrophobic interaction which shows antidiabetic activity (51).…”
Section: P Rajkumar Et Al Have Reported Antidiabetic a C T I V I T Y C O M P O U N D S F R O M T H E F L O W E R S O Fmentioning
confidence: 99%
“…Results showed an increase in sucrose activity in 60‐days old chicks, while maltase activity was not affected (Lasheras, Cenarruzabeitia, Fontan, Lluch, & Larralde, 1980). Recently, Choudhary and Mishra (2017) studied the inhibitory potential of V. faba crude seed extracts on the activities of α‐amylase. The acetone and methanol extract of the seeds showed the highest α‐amylase inhibitory activity with IC 50 = 2.94 and 5.27 mg/mL, respectively.…”
Section: Pharmacological and Biological Activities Of Vicia Plantsmentioning
confidence: 99%
“…Nevertheless, an in silico study showed that the polyphenolic compounds present in the seeds bound with the catalytic residues of the α‐amylase enzyme by hydrogen bonding and hydrophobic interaction (Choudhary & Mishra, 2017). In addition, the oral administration of V. faba pods methanol extract at a dose of 500 mg/kg body weight in alloxan‐induced diabetic mice, resulted in a decrease in the elevated levels of serum alanine aminotransferase (ALA), aspartate aminotransferase, and alkaline phosphatase activities, and urea, uric acid, and creatinine.…”
Section: Pharmacological and Biological Activities Of Vicia Plantsmentioning
confidence: 99%